The Methodology of Professional Competencies Formation for The Specialists in Environmental Monitoring on the Basis of Synergistic Pedagogics - Bordiug, Natalia; Alpatova, Oksana; Ishchuk, Oksana; Svitelskyi, Mykola; Smagly, Viktor (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The issues of professional training for future environmental engineers training are considered in the article. The methodical bases of teaching environmental monitoring have been developed and substantiated for the application in the learning process through the implementation of interdisciplinary approach. The basic components of training future environmental engineers have been defined and analysis of the formation of professional system-modeling competencies in environmental monitoring have been conducted.
Keywords: integrated education; professional competences; interdisciplinary connections; environmental monitoring